PENERAPAN BUKU PRAKTEK UBUDIYAH SSKU (STANDAR SISWA KADER ULAMA) DALAM MENUNJANG PEMBELAJARAN PAI - Durrotun Nafisah; Imam Athoir Rokhman (STAI Ma'had Aly Al-Hikam Malang, 2024)
The implementation of SSKU (Standard Student Cadre of Ulama) ubudiyah activities as a support for Islamic Religious Education (PAI) learning at MA Almaarif Singosari. This research aims to: (1) Identify the content of the material in the SSKU ubudiyah practice book, and (2) Analyze how the book is implemented at MA Almaarif Singosari. This research used a descriptive qualitative approach, with data obtained through interviews, observation, and documentation. The data were then analyzed qualitatively to describe the application of SSKU. The results showed that: (1) The content of the material in the SSKU ubudiyah practice book is considered good because it covers the cognitive, affective, and psychomotor aspects of students at each level of education (ula, wustho, and 'ulya). (2) The implementation of the SSKU book goes through three main stages: planning (determining objectives, procedures, and schedules), implementation (including memorization activities, explaining, and individual and group practice), and annual evaluation to assess the implementation and success of the SSKU book as needed.